Workplace violence in Bangladesh's garment industry. (August 2019) - Gibbs, Andrew; Jewkes, Rachel; Willan, Samantha; Al Mamun, Mahfuz; Parvin, Kausar; Yu, Marat; Naved, Ruchira
Abstract: Workplace violence (WPV) is widely reported in the Bangladeshi garment industry, impacting women workers' health and wellbeing. We explore factors associated with female workers experience or witnessing of WPV and perpetration by managers, in eight Bangladeshi garment factories. We hypothesise workers' experience of WPV is associated with i) individual factors, potentially impacting productivity (age, depression, length of work, and disability/functional limitations), ii) experience of intimate partner violence (IPV), and iii) factory culture (management styles, and adherence to laws around workers' rights). We hypothesise that managers' perpetration of emotional WPV is associated with their perceptions of female workers (indicated by their patriarchal gender attitudes and hierarchal attitudes), and whether they experience work related stress and burnout. Cross-sectional data were collected from eight self-selecting garment factories in Bangladesh, between September and December 2016 (800 female workers, 395 managers). Data were analysed with multivariable linear regression modelling. In the past four weeks, 73.5% of workers reported experiencing or witnessing physical or emotional WPV, while 63.5% of managers reported perpetrating emotional WPV. Workers' experience or witnessing of WPV was associated with more depressive symptoms (β 0.04, 95%CI 0.01, 0.07), more functional limitations (moderate limitations β 1.32 95%CI 0.22, 2.42), experience of IPV (β 2.78 95%CI 2.11, 3.44), and factory culture (challenges accessing leave (β 3.69 95%CI 2.68, 4.70), and perceptions of more coercive management practices (β 0.41 95%CI 0.32, 0.50). Managers' perpetration of emotional WPV was associated with higher levels of burnout (β 0.02 95%CI 0.01, 0.04), and more hierarchical attitudes towards workers (β 0.33 95%CI 0.21, 0.45). These findings suggest the global manufacturing regime of 'Just-in-Time' (JIT) production, emphasising short-turnaround times and high levels of productivity, combined with hierarchical attitudes towards workers, are important factors shaping WPV. Highlights: Experience of workplace violence (WPV) was associated with depression. WPV was also associated with intimate partner violence and struggles accessing leave. Managers' perpetration of WPV was associated with burnout and hierarchical attitudes. WPV is potentially associated with Just In Time regimes of production.